مشاركة المرأة الجزائرية في الحراك الشعبي وانعكاساته المحتملة على تعزيز مكانتها في العملية السياسية - مالكي, مريم; محمدي, صليحة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تعتبر المشاركة السياسية أحد ركائز الديمقراطية التشاركية، فإنها تقتضي مشاركة كل المواطنين في العملية السياسية دون تمييز بين الجنسين في اختيار الحكام والممثلين في الهيئات المنتخبة، والمشاركة في رسم السياسات العامة وصنع القرارات، إذ تبذل في هذا الصدد جهود كبيرة لتفعيل دور المرأة في الحياة السياسية وتمثيلها في المؤسسات السياسية على المستوى المحلي والوطني. ورغم أن المرأة الجزائرية كانت ضمن الأطراف المشاركة في الحراك السياسي، الذي بدأ في فيفري 2019، وخروجها للشارع معبرة عن رأيها الرافض للوضع الاجتماعي والسياسي في البلاد كمحاولة لإسماع صوتها الداعم لفكرة التغيير وتكريس التشاركية في العملية السياسية في إطار قيم ومبادئ الديمقراطية، إلا أن مشاركتها السياسية لم تصل بعد درجة التحقيق الفعلي، بما يتطلب تفعيلها كونها ضرورة للديمقراطية وعاملا رئيسا لترسيخها في الجزائر. Abstract: The political participation as one of the pillars of participatory democracy, it requires the participation of all citizens in the political process Without discrimination between the sexes in choosing rulers and representatives in elected bodies, and participating in public policy-making and decision-making. Major efforts are made in this regard to activate the role of women iin political life and their representation in political institutions at the local and national levels. Although Algerian women were among the parties participating in the political movement, which began in February 2019, and their exit to the street, as an attempt to make her voice supportive of the idea of change and the consolidation of participation in the political process within the framework of the values and principles of democracy, her political participation It has not yet reached the degree of actual investigation, which requires its activation, as it is a necessity for democracy and a major factor for its consolidation in Algeria.